Entity-relationship approach : the core of conceptual modelling - Kangassalo, Hannu ed. (North-Holland AmsterdamNL, 1991)
Addresses four major themes viz. knowledge presentation; conceptual modelling and database design; new approaches in database management systems and in information systems; and innovative theories and applications.